Salam As Banking Financing for Agriculture in Developing Countries: Lessons From Sudan - Salih Mustafa Ahmed Mualley; Issa Salim Moh'd (International Journal of Islamic Economics and Finance (IJIEF), 2022)
The objective of this study is to measure the impact of commercial bank financing via Salam mode of finance on the Sudanese agricultural production and determine whether the Salam mode is suitable for financing agriculture or not.  For the purpose of the analysis, the ordinary least squares method (OLS) was applied to a log - linear form of a simple regression model with a time series data on Sudan’s total annual agricultural production as a dependent variable and the commercial banks total annual financing via Salam for explanatory variable. The empirical results indicated that Salam mode of finance is appropriate for financing agriculture in Sudan due to its significant effects on agricultural production with a significant and positive relationship. In addition, agricultural sector highly contributed to the country economy during the study period and highly positively elastic to bank financing. However, it is hindered by heavy direct and indirect taxes, high marketing cost, long distance with poor rural infrastructure and weak agricultural returns. Therefore, relevant policy implications for both agriculture and bank financing are required. Hence, results of study suggest that banks should increase the provision for Salam mode for high agricultural production, reduce tax burdens, renovate the infrastructure, and facilitate financing procedures to agricultural sector.